Upaya Guru PAI dalam Meningkatkan Kecerdasan Spiritual Peserta Didik di SMA Al-Ma'soem - Novitasari, Ita; Fahrudin, Fahrudin; Fakhruddin, Agus (Yayasan Rahmat Islamiyah, 2024)
Spiritual intelligence occupies an important position to build and construct a person to be better and useful in dealing with and interpreting issues of meaning and value. This study aims to examine how PAI teachers' efforts in improving students' spiritual intelligence through PAI learning. A qualitative approach with a descriptive method was chosen to gain an in-depth understanding of the problem and describe it as it is.Â The findings in this study include efforts to understand the condition of students' spiritual intelligence level by means of observation, communication, and evaluation. The indicators can be seen from the practice of diversity, daily behavior, and evaluation of students. In designing PAI learning, it is adjusted to the learning outcomes and learning objectives. The PAI learning process is carried out by integrating spiritual principles and incorporating PAI aspects. The methods used must also support efforts to increase students' spiritual intelligence. After knowing the condition of the level of students, efforts are made to improve adjusted to the classification of high or low spiritual intelligence conditions. The last stage is the measurement process to determine the impact that occurs after making efforts to improve the spiritual intelligence of students.